Why has Not There been More Research of Concern? - Rappert, Brian (Frontiers in Public Health, 2014)
Amid the renewed concern in the last several years about the potential for life science research to facilitate the spread of disease, a central plank of the policy response has been to enact processes for assessing the risks and benefits of “research of concern.” The recent controversy regarding a proposed redaction of work on the modification of a H5N1 avian influenza virus is perhaps the most prominent such instance. And yet, a noteworthy feature of this case is its exceptionalness. In the last 10 years, life science publishers, funders, and labs have rarely identified any research as “of concern,” let alone proposed censors. This article takes this experience with risk assessment as an invitation for reflection. Reasons for the low number of instances of concern are related to how the biosecurity dimensions of the life sciences are identified, how they are described, how the assessments of benefits and risks are undertaken, how value considerations do and do not enter into assessments, as well as the lack of information on the outcomes of reviews. This argument builds on such considerations to examine the limitations and implications of the risk–benefit experiment of concern framing, the politics of expertise as well as the prospects for alternative responses.